曹洞宗における血盆経信仰の受容： 新出資料『血盆経因縁 侍者比丘記』を例に [Reception of Ketsubon-kyō (Bloody Pond Sutra) in Japanese Sōtō Zen School: Insights from a Newly Discovered Manuscript] - Sobczyk, Małgorzata (Silva Iaponicarum, 2024)
This paper provides new insights into the reception of Ketsubon-kyō (Bloody Pond Sutra) within the Sōtō Zen tradition, focusing on a recently-obtained anonymous manuscript titled Ketsubon-kyō Innen (Circumstances Surrounding the Emergence of Bloody Pond Sutra). Building upon previous research (Nakano Yūshin, Nakano Jūsai, Kōdate Naomi) that confirms strong associations between the Bloody Pond Sutra and Buddhist ceremonies of bestowing precepts (jukai-e), this paper argues that the manuscript contains a draft of a sermon delivered (or meant to be delivered) in two sessions to attendants of such a ceremony held at an unidentified temple – suggested by certain details to be located in Kyoto or its vicinity. Written by a person who identifies himself merely as a temple servant (jisha biku), it offers a unique synthesis of materials addressing women's impurity caused by blood and their potential for salvation. It primarily combines two texts with diverse origins: Ketsubon-kyō wage (Japanese Exposition of Bloody Pond Sutra), a lengthy commentary from 1713 by Shōyo Ganteki from the Pure Land School (Jōdoshū), and Ketsubon-kyō engi (An Account of the Origin of Bloody Pond Sutra) popularized in the late eighteenth century through woodblock-printed booklets by Shōsen-ji (previously known as Hosshō-ji), a prominent center of the Ketsubon-kyō cult within the Sōtō Zen School. With this presentation of the manuscript, this paper sheds light on the reception and interpretation of Ketsubon-kyō within the Sōtō Zen School. It demonstrates a common understanding of the role of the Bloody Pond Sutra, transcending sectarian differences to the extent of reusing exegetical materials from the Pure Land School in Zen preaching.